STABILITY OF PREFERENCES FOR END OF LIFE TREATMENT AFTER 3 YEARS OF FOLLOW-UP: THE JOHNS HOPKINS PRECURSORS STUDY - Wittink, Marsha N. (2008)
BACKGROUND: Preferences for life-sustaining treatment elicited in one state of health may not reflect preferences in another state of health. OBJECTIVE: We estimated the stability of preferences for end-of-life treatment over 3 years and whether decline in physical functioning and mental health were associated with change in preferences for end-of-life treatment. DESIGN: Mailed survey of older physicians. SETTING: Longitudinal cohort study of medical students in the graduating classes from 1948 to 1964 at Johns Hopkins University. PARTICIPANTS: 818 physicians who completed the life-sustaining treatment questionnaire in 1999 and 2002 (mean age 69 years at baseline). MEASUREMENTS: Preferences for life-sustaining treatment, assessed using a checklist questionnaire in response to a standard vignette. RESULTS: While the prevalence of the three clusters of life sustaining treatment preferences remained stable over the 3-year follow-up interval, certain physicians changed their preferences over time. The probability that physicians were in the same cluster at follow-up as at baseline was 0.41 for “most aggressive,” 0.50 for “intermediate care,” and 0.80 for “least aggressive.” Physicians without an advance directive were more likely to transition to the “most aggressive” than to the “least aggressive” cluster over the course of the 3-year follow-up (odds ratio 1.96, 95% confidence interval [1.11, 3.45]). Age at baseline and decline in physical and mental health were not associated with transitions between 1999 and 2002. LIMITATIONS: The preferences we elicited might not accurately predict treatment decisions during actual illness. CONCLUSIONS: Our findings suggest that periodic re-assessment of preferences are most critical for patients who desire aggressive end of life care or do not have advance directives. (261 words)